The evaluation of (social-)psychological comfort in clothing, a possible approach - Matté, L. L. (2017)
This paper presents the first results of a PhD research on psychological comfort of clothing. In order to understand and conceptualize the psychological aspects of clothing comfort, a variation of the Delphi Method was used to seek opinions from experts. This method was chosen because of its consensus-building features. The results were obtained from a qualitative text analysis, conducted over the experts’ responses to the first round of questions. The analytic process shed some light on the formation of the psychological comfort concept as well as the potential attributes to be evaluated when assessing this comfort dimension.